2018
DOI: 10.1039/c8an00819a
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared incoherent broadband cavity enhanced absorption spectroscopy (NIR-IBBCEAS) for detection and quantification of natural gas components

Abstract: The principle of near-infrared incoherent broadband cavity enhanced absorption spectroscopy was employed to develop a novel instrument for detecting natural gas leaks as well as for testing the quality of natural gas mixtures. The instrument utilizes the absorption features of methane, butane, ethane, and propane in the wavelength region of 1100 nm to 1250 nm. The absorption cross-section spectrum in this region for methane was adopted from the HITRAN database, and those for the other three gases were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The estimation of measurement uncertainty in the retrieved extinction coefficients of aerosols from Equation (1), was carried out using a standard propagation of errors (Varma et al 2009;Prakash et al 2018). The uncertainty in the extinction coefficient DE was calculated from…”
Section: Error Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The estimation of measurement uncertainty in the retrieved extinction coefficients of aerosols from Equation (1), was carried out using a standard propagation of errors (Varma et al 2009;Prakash et al 2018). The uncertainty in the extinction coefficient DE was calculated from…”
Section: Error Analysismentioning
confidence: 99%
“…This simple, cost effective method does not require mode matching, which makes it suitable for field measurements. IBBCEAS has been effectively used to quantify trace gases like NO 2 (Ball, Langridge, and Jones 2004), NO 3 (Suhail et al 2019;Ball, Langridge, and Jones 2004;Venables et al 2006), I 2 (Dixneuf et al 2009;Ball, Langridge, and Jones 2004), HONO (Gherman et al 2008), glyoxal (Washenfelder et al 2008), natural gases (Prakash et al 2018), 1,4-dioxane (Chandran and Varma 2016), etc. in both laboratory and in-situ field measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Laser absorption spectroscopy has been demonstrated for accurate HCl and other gas species amount fraction measurements in a variety of applications. [7][8][9][10][11][12][13][14] So far, reports on laser spectroscopic measurements of HCl in biomethane, addressing traceability of the results to the international system of units (SI), are lacking. Direct tunable diode laser absorption spectroscopy (dTDLAS) and wavelength modulation spectroscopy ((WMS) with comparably higher sensitivity 2,9 ) specifically as demonstrated in other applications 2,8,9,11 are good candidates for the development of test methods for HCl concentration measurements in biomethane.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Chandran et al reported a SC-based NIR-IBBCEAS setup to record the absorption of 1,4-dioxane using a 644-cm-long cavity consisting of two highly reflective mirrors (99.9%), leading to a detection limit of 8 × 10 –8 cm –1 in a 120 min averaging time . In 2018, Prakash et al developed a NIR-IBBCEAS sensor for the detection of natural gas mixtures, and a detection limit (3σ) of 460 ppmv, 141 ppmv, 175 ppmv, and 173 ppmv for methane (CH 4 ), butane (C 4 H 10 ), ethane (C 2 H 6 ), and propane (C 3 H 8 ), respectively, was achieved . In our previous work, an NIR-IBBCEAS sensor system in combination with a Fourier-transform spectrometer was developed for high-resolution CH 4 detection.…”
mentioning
confidence: 99%